TAHLIL MUHTAWA KITAB AL-ʿARABIYYAH BAYNA YADAYK AL-JUZʼ AL-AWWAL, AL-WIHDAT (1–8) MIN MANZUR WIZARAT AT-TARBIYYAH WA-AT-TAʿLIM AL-INDUNISIYYAH WA QIYAM AHL AS-SUNNAH WA-AL-JAMAʿAH AN-NAHDIYYAH - Ersa Antika Rahmandha; Kholida Nur; M. Agus Mushodiq (El-Tsaqafah : Jurnal Jurusan PBA, 2026)
This study aims to analyze the content of Al-‘Arabiyyah Baina Yadaik, Part One (Units 1–8), from the perspectives of the Indonesian Ministry of Education and Culture and the Ahl al-Sunnah wa al-Jamaʿah an-Nahdiyyah theoretical framework. Employing a qualitative research design with content analysis, data were collected through library research using listening and note-taking methods on instructional materials, dialogues, illustrations, and the presentation of exercises in the textbook. The findings reveal that Al-‘Arabiyyah Baina Yadaik, Part One (Units 1–8), is generally suitable for Arabic language instruction in Indonesia. The textbook demonstrates a systematic and well-organized structure, clear design, and appropriate readability for beginner learners. It adopts a communicative approach that develops the four language skills and implicitly incorporates moderate Islamic values such as tolerance, balance, and moderation. However, notable limitations include implicit gender bias in visual representations that predominantly depict males in professional and public roles. The printed version also lacks sufficient visual elements and decorative features, resulting in visually monotonous pages. The digital version preserves the print content but suffers from low image resolution when enlarged, a static non-responsive layout, inadequate font and color design for fully vocalized Arabic text, and a lack of interactive features such as digital navigation, vocabulary highlighting, and interactive exercises, reducing its effectiveness for online learning. This study contributes to the development of a comprehensive evaluation model for international educational textbooks as transformative media in promoting moderate Islamic values and recommends the necessity of contextual content adaptation by teachers.